A simplified and fast computational finite element model for the nonlinear load-displacement behaviour of reinforced concrete structures. (15th June 2018) - Benakli, S.; Bouafia, Y.; Oudjene, M.; Boissière, R.; Khelil, A.
Abstract: Numerical simulation of reinforced concrete structures requires the explicit representation of both the concrete and the reinforcement bars, where the two materials are modelled separately using appropriate constitutive laws including damage variables for concrete in compression and tension. Even if this way of modelling is convenient and satisfactory, it requires a huge computational effort especially in the case of large scale applications. The aim of this paper is to develop an alternative model dedicated for the simulation of large scale reinforced concrete structures with no need to represent explicitly the steel reinforcements. Based on the literature review, the authors developed a fictitious stress–strain relationship for reinforced concrete under tension. The model is based on the shape of the slip-adhesion curve between steel and concrete proposed by the European Committee for Concrete (C.E.B.) to estimate the crack opening widths. Relationships covering the cracked stage up to the yield point of the steel are proposed depending on the material properties of concrete and steel, on the reinforcement ratio, as well as on the crack widths. The developed model was successfully implemented in the ABAQUS commercial software. The effectiveness and computational efficiency are demonstrated through some examples under tensile and bending loadings.